Systematic Case-Based Analysis of the Maurora® Drug-Eluting Stent in Vertebral Artery Intervention - Gao, Shenghan (Transactions on Environment, Energy and Earth Sciences, 2026)
Drug-eluting stent(DES) has reduced the rate of (ISR) and improved Vessel patency rate dramatically since it came out in 2002. However,the structure of vertebral artery is complex and has high rate of ISR, which causes a restriction of conventional bare-metal stent (BMS) and off-label coronary stents at this site. Maurora® sirolimus-eluting stent, as the first DES approved for vertebral artery indication all over the world, marked an important breakthrough in the field of neurointervention. This essay uses a systematic case-based approach to analyze the fluoropolymer coating design, drug-release mechanism, clinical performance, and practical challenges of the Maurora® stent. In a word, Maurora® deals with the challenges effectively in treating vertebral artery stenosis and provided a reference for the future optimization and development of DES in the neurovascular field, through the combined design of alloy material optimization, fluorinated coating, and drug-release system. Future direction may develop bioadaptive coatings and combination strategies to reduce restenosis and enhance neurovascular outcomes.
Keywords: Vertebral artery; drug-eluting stent; in-stent restenosis.